A contiguous de novo genome assembly of sugar beet EL10 (Beta vulgaris L.). (5th October 2022) - McGrath, J Mitchell; Funk, Andrew; Galewski, Paul; Ou, Shujun; Townsend, Belinda; Davenport, Karen; Daligault, Hajnalka; Johnson, Shannon; Lee, Joyce; Hastie, Alex; Darracq, Aude; Willems, Glenda; et al.
Abstract: A contiguous assembly of the inbred 'EL10' sugar beet ( Beta vulgaris ssp. vulgaris ) genome was constructed using PacBio long-read sequencing, BioNano optical mapping, Hi-C scaffolding, and Illumina short-read error correction. The EL10.1 assembly was 540 Mb, of which 96.2% was contained in nine chromosome-sized pseudomolecules with lengths from 52 to 65 Mb, and 31 contigs with a median size of 282 kb that remained unassembled. Gene annotation incorporating RNA-seq data and curated sequences via the MAKER annotation pipeline generated 24, 255 gene models. Results indicated that the EL10.1 genome assembly is a contiguous genome assembly highly congruent with the published sugar beet reference genome. Gross duplicate gene analyses of EL10.1 revealed little large-scale intra-genome duplication. Reduced gene copy number for well-annotated gene families relative to other core eudicots was observed, especially for transcription factors. Variation in genome size in B. vulgaris was investigated by flow cytometry among 50 individuals producing estimates from 633 to 875 Mb/1C. Read-depth mapping with short-read whole-genome sequences from other sugar beet germplasm suggested that relatively few regions of the sugar beet genome appeared associated with high-copy number variation.